Characteristics of the Intestinal Microbiota in Very Low Birth Weight Infants With Extrauterine Growth Restriction - Li, Hongping; He, Zhijiang; Gao, Di; Lv, Yuanhong; Zhou, Queyun; Xiao, Bin; Huang, Weimin (Frontiers in Pediatrics, 2019)
Objective: Very low birth weight (VLBW) infants, which experience significant postnatal growth restriction at the time of discharge, are at high risk of later growth failure and long-term consequences. This study aims to characterize the structure of intestinal microbiome community in VLBW infants with extrauterine growth restriction (EUGR). Methods: 23 VLBW infants appropriate for gestational age hospitalized at the neonatal intensive care unit of the BaoAn Maternal and Child Care Hospital (Shenzhen, China) were enrolled in this study, which were divided into the growth restriction group (EUGR; n = 12) and the normal growth group (AGA; n = 11). Meconium and fecal samples at postnatal day 28 were collected respectively during hospitalization. Total bacterial DNA was extracted and sequenced using the Illumina MiSeq Sequencing System based on the V3-V4 hyper-variable regions of the 16S rRNA gene. Results: The intestinal bacterial communities of preterm infants were dominated by the phylum Proteobacteria. Compared with the AGA group, the relative abundances of the genera Aeromicrobium and Serratia in meconium samples significantly decreased, whereas genera Parabacteroides, Ruminococcus, Blautia, and Aeromonas were more prevalent in the EUGR group. On postnatal day 28, the relative abundances of the genera Parabacteroides, Bacteroides, Eubacterium, Granulicatella and Salinivibrio were significantly different between the two groups, where genus Salinivibrio decreased significantly in the EUGR samples. Among them, genus Parabacteroides was more abundant on both postnatal day 1 and day 28. Further KEGG prediction analysis showed that there were many differences in functional genes and pathways between the two groups on postnatal day 28, but not on day 1, the majority of which were related to energy metabolism. And no statistical differences were observed in the clinical characteristics of infants. Conclusions: Overall, these findings showed that a distinct gut microbiota profile presented in preterm infants with extrauterine growth restriction. The role of intestinal microbiome in the extrauterine growth of preterm infants during hospitalization should be further investigated.